Strengthening the health surveillance of marine mammals in the waters of metropolitan France by monitoring strandings - Wund, S.; Méheust, E.; Dars, C.; Dabin, W.; Demaret, F.; Guichard, B.; Jauniaux, T.; Labrut, S.; Spitz, J.; Van Canneyt, O.; Caurant, F. (Frontiers in Marine Science, 2023)
Monitoring the health status of marine mammals is a priority theme that France aims to develop with the other European Union Member States in the next two years, in the context of the Marine Strategy Framework Directive. With approximately 5,000 km of coastline and for nearly ten years, France has been recording an average of 2,000 strandings per year, which are monitored by the National Stranding Network, managed by Pelagis, the observatory for the conservation of marine mammals from La Rochelle University and the French National Center for Scientific Research. Since 1972, this network has successively evolved from spatial and temporal faunistic description to, nowadays, the detection of major causes of mortality. It now aims to carry out epidemiological studies on a population scale. Thus, a strategy to strengthen the monitoring of marine mammals’ health status based on stranding data has been developed. This strategy will allow for a more accurate detection of anthropogenic cause of death as well as those of natural origin. It will allow the monitoring of time trends and geographical differences of diseases associated with conservation and public health issues while ensuring the early detection of emerging and/or zoonotic diseases of importance. It will also allow a better assessment of the consequences of human activities on these animal populations and on the environment. Thus, this strategy is fully in line with the “One Health” approach which implies an integrated vision of public, animal and environmental health. It is broken down into four surveillance modalities: (1) general event-based surveillance (GES); (2) programmed surveillance (PS); (3) specific event-based surveillance (SES); (4) and in the longer term, syndromic surveillance (SyS). This article describes the French strategy as well as these different surveillance modalities, the levels of examinations and the associated sampling protocols and finally, the method of standardisation of the data collected. The objective is to present the strategy developed at the French level in order to integrate it into a future strategy shared at the European level to standardise practices and especially complementary analysis, necessary for a better evaluation of the health status of these mobile marine species.